4(x+2)=5-(x-2)

Simple and best practice solution for 4(x+2)=5-(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+2)=5-(x-2) equation:


Simplifying
4(x + 2) = 5 + -1(x + -2)

Reorder the terms:
4(2 + x) = 5 + -1(x + -2)
(2 * 4 + x * 4) = 5 + -1(x + -2)
(8 + 4x) = 5 + -1(x + -2)

Reorder the terms:
8 + 4x = 5 + -1(-2 + x)
8 + 4x = 5 + (-2 * -1 + x * -1)
8 + 4x = 5 + (2 + -1x)

Combine like terms: 5 + 2 = 7
8 + 4x = 7 + -1x

Solving
8 + 4x = 7 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
8 + 4x + x = 7 + -1x + x

Combine like terms: 4x + x = 5x
8 + 5x = 7 + -1x + x

Combine like terms: -1x + x = 0
8 + 5x = 7 + 0
8 + 5x = 7

Add '-8' to each side of the equation.
8 + -8 + 5x = 7 + -8

Combine like terms: 8 + -8 = 0
0 + 5x = 7 + -8
5x = 7 + -8

Combine like terms: 7 + -8 = -1
5x = -1

Divide each side by '5'.
x = -0.2

Simplifying
x = -0.2

See similar equations:

| 0.6(x-2)=12.0 | | 8x+8-5x=3x+8 | | 7n=77 | | 12x-3=90+3(x-7) | | n-12=10 | | 3x+4=6-7x | | 10x^2+1=11X | | -5(n+3)-(7+8n)= | | 2(e-15)=32 | | 3x(-3x+5)=5 | | 37x+20=0 | | x(2-x)(2+x)-x-2= | | 4+x^2=75 | | 5(3X-4)=16x | | 11-(x+8)=3+x | | 11+n=-5 | | 43-7x=2x+18 | | 8y+6=38 | | 11+n= | | -6-4n+3n=20-35 | | -15-13d=-15d+15 | | 8y+6=42-4 | | 6x^2+5+1= | | X^2+8x-71=0 | | .666666667+3y=5y-.133333333 | | 5-10x=777-31x | | (x-9)5= | | 8(w+5)=5w+19 | | -y=-5 | | ax+bx+5=10 | | 5(x+2)=32 | | -15x+18=-7x-6 |

Equations solver categories